The Case for Moral Consumption: Examining and Expanding the Domain of Moral Behavior to Promote Individual and Collective Well-Being. (September 2016) - Komarova Loureiro, Yuliya; Bayuk, Julia; Tignor, Stefanie M.; Nenkov, Gergana Y.; Baskentli, Sara; Webb, Dave
This research delineates and critically examines extant empirical research on marketplace morality within the context of transformative consumer research. The authors identify how public policy can be leveraged to promote moral consumption in the marketplace in line with the transformative consumer research objectives of personal and collective well-being. They conduct a systematic review of the last decade of marketing literature and find that the definition of what is considered "marketplace morality" has been rather narrow. Subsequently, the authors propose a broader definition and develop a typology of moral consumption behaviors based on the valence of moral judgment/behavior (moral or immoral) and moral content (harm, fairness, loyalty, authority, and purity). The authors find that most research has focused on understanding one-time (im)moral behaviors in narrow domains, which have local implications and short-term impact. This research proposes that there is untapped potential in investigating repeated (im)moral behaviors associated with lifestyle choices and habits and that these have wider, long-term moral implications (e.g., wastefulness, overindulgence, pollution, authenticity, discrimination). Finally, the authors consider the underlying motivations for (im)moral behaviors and offer recommendations for policy development and research.